The Influence Of Motivation And Discipline On The Work Productivity Of Employees In Camat Office Of Sukaraja District, Seluma Province, Bengkulu Province - Ida Ayu Made Er Meytha Gayatri; Mimi Kurnia Nengsih (Perkumpulan Dosen Muda (PDM) Bengkulu, 2021)
The purpose of this study was to determine factors such as motivation and work discipline tahat affect the work prductivity of employees at the Head Office of Sukaraja District, Seluma Regency. The sample in this study was 29 employees at the Head Office of Sukaraja District, Seluma Regency. Data collectiion using a questionnaire and the method of analysis used is multiple linear regression, test of determination and hypothesis testing. The result of the regression equation is Y = n10,107 + 0,417 X1 + 0,361X2 + e, which means that motivation and work discipline have a positive influence of the work productivity of employees at the Head Office of Sukaraja District, Seluma Regency. The results of the determination test was 0,567 0r (56,7%). This shows that motivation and work discipline have an effect on the work productivity of employees at the Subdistrict Head Office of Sukaraja District, Seluma Regency by 56,7 % while the rest are explained or influenced by other variables not examined.